Learning to Lead: A Handbook for Postsecondary Administrators - Davis, James P. (Rowman & Littlefield Publishers, 2003)
Leadership is an activity that not only manifests itself in formal positions, but also bubbles up in various places within an organization. Perhaps given the importance of leadership to any endeavor, the literature on this topic has burgeoned. Yet among these titles, Learning to Lead stands out as one of the best texts available on leadership for college and university administrators. Critical skills such as managing people, resolving conflict, and making rational (and legal) decisions are explored within the context of the campus. The book also addresses the needs of those who facilitate leadership workshops, serve as mentors to potential leaders, and teach courses on higher education leadership and administration. While presenting all sides of key issues, the author calls for the reader to define his or her own position through a series of provocative reflection questions in each chapter. Thus the book invites interaction and teaches administrators not what to think about leadership, but how to think about it.